Thermal modeling of Vanadium redox flow battery - Jia, Junduo (2013)
In this report, the vanadium redox flow battery is introduced. Thermal modeling is one important issue to the battery. A dynamic thermal model of this battery is developed to investigate the stack and tank temperature changes under different conditions and input variables. In this model, the power loss due to battery internal resistance, the chemical power loss and the pump power loss are all considered. The principle of conservation of energy is applied to derive the equations which are used to develop this model. Furthermore, the state space model is utilized to perform the simulations. Matlab programming is used to perform the simulations. The results show that the temperature of the battery is very sensitive to the structure of the hydraulic circuits and the electrolyte flow rate. The power loss due to internal resistance increases quadratically with increasing of current.